Efficacy of acupuncture for motor dysfunction in early Parkinson’s disease: protocol for a randomized, single-blind, sham-controlled clinical trial - Li, Qifu; Shen, Yuquan; Wang, Yangyang; Liu, Junxia; Chen, Ziwen; Luo, Weiming; Chen, Yan; Liu, Yunnan; Zhu, Xinghua; Xue, Simin; Chen, Yanru; Li, Dehua; et al. (Frontiers in Medicine, 2025)
IntroductionMotor dysfunction, including bradykinesia, rigidity, tremor, and gait disturbance, is the core clinical feature of Parkinson’s disease (PD) and a major cause of disability. In early-stage PD (Hoehn and Yahr ≤2.5), neurodegeneration is relatively mild, and timely intervention may help preserve motor function and delay progression. Although dopaminergic medications effectively alleviate motor symptoms, their long-term use is associated with motor fluctuations and levodopa-induced dyskinesia. Acupuncture, a low-risk, well-tolerated intervention, has shown potential in improving motor performance in PD, but high-quality evidence in early-stage patients is lacking.Methods and analysisThis single-blind, sham-controlled randomized clinical trial will enroll 120 patients with early-stage PD (disease duration ≤3 years). Participants will be randomly assigned in a 1:1 ratio (n = 60 per group) to the true acupuncture (TA) or sham acupuncture (SA) group using stratified block randomization (block size 4) by study center. Treatment will be administered three times weekly for 12 weeks, with follow-up to 15 months. The primary outcome is the change in composite clinical motor score (CCMS) from baseline to week 12. The secondary outcomes include Movement Disorder Society unified Parkinson’s disease rating scale (MDS-UPDRS), Purdue Pegboard Test score (PPTS), Timed Up and Go Test (TUG), 6-min walk test (6MWT), Non-Motor Symptoms Scale (NMSS), 39-item Parkinson’s Disease Questionnaire (PDQ-39), Clinical Global Impression Scale (CGI), and levodopa equivalent daily dose (LEDD). Acupuncturists will not be blinded while participants, outcome assessors, and data analysts remain blinded. The primary analysis will use intention-to-treat (ITT) with mixed-effects models for longitudinal changes, handling missing data via multiple imputation by chained equations.DiscussionThis study aimed to evaluate the efficacy and safety of acupuncture in improving motor function in early-stage PD. The results will help determine its potential role as an adjunctive therapy to preserve motor function.Clinical trial registrationhttps://itmctr.ccebtcm.org.cn/, identifier ITMCTR2025001290.